Policies and practices in Italian welfare housing : Turin, up to the current neo-liberal approach and social innovation practices - Caruso, Nadia (Springer, 2017)
This book offers a European perspective on urban planning and spatial design by outlining housing policies in Southern Europe and their evolution. Through a unique case study on the city of Turin it explores social innovation and the relationship between the urban regeneration process and housing practices. The case study is a useful example in the debate about changing welfare arrangements in Europe and the emerging rhetoric of social innovation in housing. The book encourages debate about the tools needed to address housing needs, exploring current practices. Chapters look at the spatial dimension of housing, the financial mechanisms put in place, the actors involved in the field (public authorities, ethical investors, tertiary sector, inhabitants and locals.) The case study of the metropolitan city of Turin demonstrates complex housing needs and the innovative character of public and private solutions. As this book combines theory and practice, it appeals to both academics and practitioners. It is especially be of interest to spatial planners, geographers and social scientists interested in housing policies, and those interested in the Italian context of the case study.- Resumé vydavatele
Keywords: bytová politika -- Turín (Itálie); bytová politika -- Itálie; sociální bydlení -- Turín (Itálie); housing policy -- Turin (Italy); housing policy -- Itaky; social housing -- Turin (Italy); elektronické knihy; případové studie; monografie; electronic books; case studies; monographs